A seed dispersal effectiveness framework across the mutualism–antagonism continuum - van Leeuwen, Casper H. A.; Villar, Nacho [UNESP]; Mendoza Sagrera, Irene; Green, Andy J.; Bakker, Elisabeth S.; Soons, Merel B.; Galetti, Mauro [UNESP]; Jansen, Patrick A.; Nolet, Bart A.; Santamaría, Luis (Wiley, 2022)
Many angiosperms rely on vertebrates for seed dispersal via gut passage, an interaction that has been traditionally classified as a mutualism. The seed dispersal effectiveness (SDE) framework provides a mechanistic approach to evaluate evolutionary and ecological characteristics of animal-mediated seed dispersal, by synthesising the quantity and the quality of the dispersal that a plant species receives from each of its animal dispersers. However, the application of the SDE framework has been largely restricted to plant–frugivore interactions, whereas animal-mediated seed dispersal results from plant–disperser interactions that cover a continuum from pure mutualisms to antagonisms. This biases ecological and evolutionary knowledge on plant–disperser interactions. Here, we propose an extended SDE framework (‘eSDE') that allows comparing plant–disperser interactions in the full mutualism–antagonism continuum ranging from pure mutualisms (frugivores) to conditional mutualisms (scatter-hoarding granivores and folivores) and antagonisms (pure granivores). We present the eSDE framework, and use examples to illustrate how it can be applied to compare effectiveness among plant–disperser interaction types. Our initial comparison based on available data suggests that vertebrate species differ more in the number of seeds they deposit away from the mother plant (quantity), than in the effects such dispersal processes have on seed fate (quality). Scatter-hoarding granivores provide the most effective dispersal due to high removal rates, closely followed by frugivores due to high deposition rates. Folivores and pure granivores provide low quantity dispersal, but of high and moderate quality, respectively. These early comparative insights illustrate the necessity and usefulness of more standardized data collection protocols, for which we provide recommendations. Applying the eSDE framework can reveal broad-scale patterns across and within plant–disperser interaction types, which will advance our evolutionary understanding of plant–animal interactions. This will provide new insights into the consequence of anthropogenic impacts on vertebrate-mediated seed dispersal in a world in which plant–animal interactions are increasingly threatened.
Keywords: eSDE framework; folivory; frugivory; granivory; plant–animal interaction; scatter-hoarding